Кафа і Тана в системі італійської міжнародної торгівлі XIII-XV ст. - Господаренко, О.В. (Історичний архів. Наукові студії, 2014)
Проаналізовано роль провідних центрів італійської торгівлі у чорноморському регіоні –
генуезької Кафи та венеційської Тани – в системі італійської міжнародної торгівлі XIII –
XV ст. Проанализирована роль ведущих центров итальянской торговли в черноморском
регионе – генуэзской Каффы и венецианской Таны – в системе итальянской
международной торговли XIII – XV вв. During many centuries the Northern Black Sea and the Crimea were in the center of Intercontinental trade relations between Europe and Asia. In XIII – XV centuries the main role in these processes played Italian Maritime Republic – Genoa and Venice. Due to the trading activities of Italian merchants, trading in the Black Sea region has become a brand new one: from regionally locked it started correlating with the global trade communications.